Facts and proofs diagnostic test and structural communication grid test on the topic of bacteria: A quantitative analysis - Chaerul Novitasari; Murni Ramli; Puguh Karyanto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2018)
Facts and Proofs Diagnostic Test and Structural Communication Grid Test are the tests to train, improve, and assess the level of students’ conceptual understanding and argumentation skills. This research was aimed to analyze the test item of the Facts and Proofs Diagnostic Test and Structural Communication Grid Test about bacteria, constructed as the columnar structured essay. The aspects of the validity, reliability, distinguishing power, and difficulty levels were analyzed using SPSS v.2.0 and Microsoft Excel 2010. Three-hundred and fifty-one students in Sragen Indonesia were chosen as the participants, selected using proportionate stratified random sampling. The schools were selected using cluster sampling. The results showed that two items were eliminated (Q3 and Q6). Revisions for 50 columnar items and five essays have been done. About 35.48% of the items were revised and the rest (64.52%) was accepted. The revised items were six of Facts and Proof Diagnostic test items, and one of SCG item, with 82 columnar items and 18 structural essay items. The finalized instrument can be used to detect students’ conceptual understanding, misconceptions, and argumentation skill.